Teologi Rangkulan: Perspektif Pendeta Huria Kristen Indonesia tentang Kepedulian terhadap Lesbian, Gay, Biseksual dan Transgender (Jurnal Pendidikan Agama dan Teologi, 2025)
This research is entitled "Theology of Embrace: Perspectives of Indonesian Christian Pastors on Concern for Lesbian, Gay, Bisexual, and Transgender People." The focus of the research is directed at how pastors of the Indonesian Christian Church (HKI) understand and respond to the presence of the LGBT community within the congregation, as well as how the concept of embrace theology can be implemented in Church services. The background of this research arises from the persistence of stigma, discrimination, and rejection of LGBT people in the church environment, which impacts their alienation from fellowship. This research method uses a qualitative with a descriptive approach, the researcher interviewed 10 HKI pastors in 9 regions to explore their perspectives. The results show that 3 HKI pastors still hold conservative views regarding LGBT, viewing it as behavior that is contrary to the values ​​of Christian faith. There are also 7 pastors who are starting to open themselves to embracing LGBT people through a more humane and compassionate pastoral approach. The concept of embrace theology according to Miroslav Volf is a relevant theological offer for creating an inclusive church space, solidarity, and relationship restoration. This research is expected to contribute to the church, especially HKI, in formulating pastoral policies that are fair, relevant, and in line with the values ​​of Christ's love for all people without exception.